2013
DOI: 10.1186/2193-1801-2-355
|View full text |Cite
|
Sign up to set email alerts
|

Association of the HLA locus and TNF with type I autoimmune hepatitis susceptibility in New Zealand Caucasians

Abstract: PurposeThe precise etiology of autoimmune hepatitis (AIH) remains unknown, although a number of genetic loci have been implicated in the susceptibility of type 1 AIH. The purpose of this study was to test for association of these loci with type 1 AIH in New Zealand Caucasians.Methods77 AIH patients and 485 healthy controls were genotyped for the SNPs rs2187668 (HLA-DRB*03:01), rs660895 (HLA-DRB*04:01), rs3749971 (HLA-A1-B8-DR3), rs231775 (CLTLA4), rs1800629 (TNF), and rs1800682 (FAS) using predesigned TaqMan S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(44 reference statements)
0
7
1
Order By: Relevance
“…; Ngu et al . ). Furthermore, environmental factors including infections with hepatitis B virus (HBV), hepatitis C virus (HCV), cytomegalovirus (CMV), herpes simplex virus (HSV) or bacteria ( Listeria monocytogenes ) (Limmer et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Ngu et al . ). Furthermore, environmental factors including infections with hepatitis B virus (HBV), hepatitis C virus (HCV), cytomegalovirus (CMV), herpes simplex virus (HSV) or bacteria ( Listeria monocytogenes ) (Limmer et al .…”
Section: Introductionmentioning
confidence: 97%
“…Approximately 45-80% of patients with AIH will progress to cirrhosis, of which 4% will develop hepatocellular carcinoma (HCC) (Czaja 1995;Mizutani et al 2005;Longhi et al 2010;Oo et al 2010). In 40% of patients with AIH, copresentation with other autoimmune disorders such as thyroiditis, ulcerative colitis, type 1 diabetes and rheumatoid arthritis and overlap syndromes including primary biliary cirrhosis, primary sclerosing cholangitis and autoimmune cholangitis is observed (Czaja 1995; Although the initial trigger causing AIH is unknown, it is widely accepted that genetic factors, such as HLA-DR3 or HLA-DR4 haplotypes, are risk factors Ngu et al 2013). Furthermore, environmental factors including infections with hepatitis B virus (HBV), hepatitis C virus (HCV), cytomegalovirus (CMV), herpes simplex virus (HSV) or bacteria (Listeria monocytogenes) (Limmer et al 1998a,b;Longhi et al 2010) and drugs such as nitrofurantoin and minocycline (Bjornsson et al 2010) can trigger hepatitis onset/development.…”
Section: Introductionmentioning
confidence: 99%
“…3,[15][16][17][18][19] No independent and reproducible associations outside the MHC have been identified. [20][21][22][23][24][25][26][27][28] Since genome-wide association studies (GWASs) have emerged as a powerful and unbiased approach for the identification of new genetic susceptibility loci in autoimmune diseases, 29 we applied this methodology in a large cohort of AIH patients and controls and replicated the identified loci in an independent set of patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“… 22 Multiple studies failed to show any significant association of the +49 A/G polymorphism with autoimmune hepatitis susceptibility and onset. In fact, a study realized 25 in New Zealand included 77 autoimmune hepatitis patients and showed no statistically significant association between the CTLA4 +49 gene polymorphism and the occurrence of autoimmune hepatitis. Other studies that have examined the implication of +49 A > G polymorphism CTLA4 (rs 231775) with AIH onset have failed to show a definitive association between CTLA4 A/G polymorphism and disease susceptibility in Brazilian, Chinese, Japanese or Netherlandic populations (Bittencourt et al.…”
Section: Discussionmentioning
confidence: 96%